Poly(acrylamide) Grafts on Spherical Polymeric Sulfonamide Based Resin for Selective Removal of Mercury Ions from Aqueous Solutions - Şenkal, Bahire Filiz; Yavuz, Erdem; Bicak, Niyazi (Wiley, 2004)
AbstractPoly (acrylamide) was grafted from carboxylic acid groups onto cross linked poly (styrene) beads using a redox polymerization methodology. A beaded polymer with a poly(acrylamide) surface shell was prepared in three steps, starting from poly(styrene‐divinyl benzene) (PS‐DVB) (10% crosslinking) based beads with a particle size of 420‐590μm, according to the synthetic protocol; chlorosulfonation, sulfamidation with glycine and grafting using a concentrated aqueous acrylamide solution with cerium ammonium nitrate.The resulting polymer resin with 220 wt % of grafted poly (acrylamide) has been demonstrated to be an efficient mercury‐specific sorbent, able to remove Hg (II) from solutions at ppm levels. The mobility of the graft chains provides nearly homogenous reactions conditions and rapid mercury binding ability. The mercury sorption capacity under non‐buffered conditions is around 5.75 mmol/g. No interference arises from common metal ions such as Cd (II), Fe (II), Zn (II), and Pb (II).The sorbed mercury can be eluted by repeated treatment with hot acetic acid without hydrolysis of the amide groups.